Anemia in patients with acute coronary syndromes treated with prasugrel or ticagrelor: Insights from the RENAMI registry. Issue 167 (July 2018) - Guerrero, Carme; Garay, Alberto; Ariza-Solé, Albert; Formiga, Francesc; Raposeiras-Roubín, Sergio; Abu-Assi, Emad; D'Ascenzo, Fabrizio; Kinnaird, Timm; Manzano-Fernández, Sergio; Alegre, Oriol; Sánchez-Salado, José C.; Lorente, Victòria; et al.
Abstract: Introduction: Ticagrelor and prasugrel are recommended as first line therapy in patients with acute coronary syndromes (ACS). However, patients with anemia are commonly treated with clopidogrel in routine clinical practice. The RENAMI registry ( REgistry of New Antiplatelet therapy in patients with acute Myocardial Infarction ) included ACS patients treated with prasugrel or ticagrelor at hospital discharge. The aim of this study was to analyze the prevalence of anemia and characteristics and outcomes of these patients according to anemia status. Methods: Consecutive patients with ACS from 11 centers were included. All patients underwent percutaneous coronary intervention (PCI). Anemia was defined as hemoglobin <130 g/L in men and <120 g/L in women. The incidence of ischemic and bleeding events and all-cause mortality were assessed at one year. Results: From 4424 patients included, 405 (9.2%) fulfilled criteria of anemia. Patients with anemia were significantly older, had a higher prevalence of peripheral artery disease, previous bleeding and renal disfunction and higher bleeding risk (PRECISE-DAPT score ≥ 25: 37.3% vs 18.8%, p < 0.001) The incidence of BARC 3/5 bleeding was moderately higher in patients with anemia (5.4% vs 1.5%, p = 0.001). The incidence of stent thrombosis or reinfarction was not significantly different according to anemia status. Anemia was independently associated with mortality (HR 1.73; 95% CI 1.03-2.91, p = 0.022). Conclusions: A not negligible proportion of patients treated with ticagrelor or prasugrel met criteria for anemia. Anemia was an independent predictor of mortality. Despite their higher bleeding risk profile, patients with anemia had an acceptable rate of bleeding. Highlights: Patients with ACS and anemia are commonly treated with clopidogrel in routine clinical practice. A not negligible proportion of patients with ACS treated with ticagrelor or prasugrel form this series met criteria of anemia (9.2%). Anemia was an independent predictor of mortality. Despite their higher bleeding risk profile, patients with anemia had an acceptable rate of bleeding at one year (5.4%).